Peran Kepemimpinan Transformasional dalam Orkestrasi Environmental, Social, Governance - Saladdin Wirawan Effendy; Poppy Indriani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to systematically analyze the role of transformational leadership in orchestrating the achievement of Environmental, Social, and Governance (ESG) performance. Using a Systematic Literature Review (SLR) approach, this research examines a range of scholarly articles that explore the relationships among transformational leadership, organizational innovation, digital leadership, green leadership, and sustainability outcomes. The findings indicate that transformational leadership is a critical determinant in shaping a sustainability vision, mobilizing organizational commitment, and stimulating pro-environmental behaviors through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The influence of transformational leadership on ESG performance operates primarily through mediating mechanisms such as organizational and green innovation, sustainability management systems (ESGM, CSR, EMA), as well as psychological mechanisms including green empowerment and environmental self-efficacy. Furthermore, digital leadership strengthens ESG orchestration by leveraging digital technologies that enhance accuracy, transparency, and accountability in sustainability reporting. Moderating factors such as external social capital, organizational inertia, and green training also shape the effectiveness of transformational leadership. Overall, this SLR highlights that transformational leadership functions as an “orchestrator” that aligns strategies, systems, innovation, technology, and employee behaviors to achieve long-term sustainability. The findings provide important implications for organizations in developing countries, including state-owned enterprises in Indonesia, in designing adaptive and competitive ESG leadership models and sustainability strategies.